ChemInform Abstract: Base‐Induced Cyclization of Propargyl Alkenylsulfones: A High‐Yielding Synthesis of 4, 5‐Disubstituted 2H‐Thiopyran 1, 1‐Dioxides. Issue 2 (23rd December 2015) - Hatial, Ishita; Das, Joyee; Ghosh, Ananta K.; Basak, Amit
Abstract: In case of sulfonamide (VIII) the dihydronaphthalene derivative (IX) is obtained through a Garratt—Braverman cyclization.